1993
DOI: 10.1128/aem.59.7.2317-2319.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazing by the Free-Living Soil Amoebae Acanthamoeba castellanii, Acanthamoeba polyphaga , and Hartmannella vermiformis on Various Bacteria

Abstract: Cultures of 10 different bacteria were used to serve as food sources for axenically grown Acanthamoeba casteUlanii, Acanthamoeba polyphaga, and HartmanneUla vermiformis. The nonpigmented enterobacteriaceae Escherichia coli K-12 and KlebsieUla aerogenes appeared to be excellent feed to all three amoebae. Hardly any growth or ammonium production was observed in tests with Chromatium vinosum and Serratia marcescens, which share the presence of pigmented compounds. Distinct differences in net ammonium production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 27 publications
3
63
0
Order By: Relevance
“…Behaviour of P. aeruginosa PA103 differs from other strict extracellular bacteria, such as Escherichia coli and Klebsiella aerogenes, which provide excellent nourishment for A. castellanii and A. polyphaga (Weekers et al 1993). Weekers et al (1993) incubated each of E. coli and K. aerogenes with each of A. castellanii and A. polyphaga in saline, which might trigger amoebae to ingest bacteria for nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviour of P. aeruginosa PA103 differs from other strict extracellular bacteria, such as Escherichia coli and Klebsiella aerogenes, which provide excellent nourishment for A. castellanii and A. polyphaga (Weekers et al 1993). Weekers et al (1993) incubated each of E. coli and K. aerogenes with each of A. castellanii and A. polyphaga in saline, which might trigger amoebae to ingest bacteria for nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour of P. aeruginosa PA103 differs from other strict extracellular bacteria, such as Escherichia coli and Klebsiella aerogenes, which provide excellent nourishment for A. castellanii and A. polyphaga (Weekers et al 1993). Weekers et al (1993) incubated each of E. coli and K. aerogenes with each of A. castellanii and A. polyphaga in saline, which might trigger amoebae to ingest bacteria for nutrients. Therefore, we cultivated A. castellanii in PBS in the absence or presence of PA103 that produces ExoS or ExoU to investigate growth and encystation of the amoebae: A. castellanii did not grow regardless of whether the examined bacterial strains were absent or present.…”
Section: Discussionmentioning
confidence: 99%
“…These amoebae interact with the various bacteria present in such environments. The nature of the interactions varies widely, from simple use of the bacteria as food sources for the amoebae (Weekers et al, 1993), to symbiotic relationships that enhance bacterial survival in the environment or that allow long-term intra-amoeba survival of bacteria, thereby also favouring their dissemination (Weekers et al, 1993;Greub and Raoult, 2004;Laskowski-Arce and Orth, 2008). Indeed, many studies have found a role of Acanthamoeba spp.…”
Section: Introductionmentioning
confidence: 99%
“…Their elongated pseudopodia comprise a more stable cytoskeletal structure that resists compression (Ueda & Ogihara, 1994), and although this is thought to aid in the drifting mechanism of these cells, the stiffened pseudopodia are not thought to provide a method of propulsion or feeding (Smirnov, 2002;Smirnov & Brown, 2004). However, growth rates of amoebae in shaken suspended systems have been reported (Weekers et al, 1993), so it remains unclear as to whether 'floating forms' can indeed feed planktonically or whether the experimental system affords a subhabitat for trophozoites to feed on attached bacteria. Attachment can occur in unshaken suspended systems, with participating organisms settling onto, or attaching to, the bottom of the container.…”
Section: Introductionmentioning
confidence: 99%